Increased Hip and Knee Flexion During Landing Decreases Tibiofemoral Compressive Forces in Women Who Have Undergone Anterior Cruciate Ligament Reconstruction. (February 2013) - Tsai, Liang-Ching; Powers, Christopher M.
Background: Those who have undergone anterior cruciate ligament reconstruction (ACLR) have been shown to exhibit increased muscle co-contraction, decreased knee flexion, and elevated tibiofemoral compressive forces. Elevated tibiofemoral compressive forces may be associated with the high risk of developing knee osteoarthritis in this population. Purpose: To examine whether muscle co-contraction and tibiofemoral compressive forces in women after undergoing ACLR can be reduced through the use of a landing strategy that emphasizes greater hip and knee flexion. Study Design: Controlled laboratory study. Methods: Ten female recreational athletes who had previously undergone ACLR participated in this study. Participants performed a single-legged drop-land task before and after a training session that encouraged them to use greater hip and knee flexion during landing. Peak tibiofemoral compressive forces before and after training were estimated using an electromyography (EMG)–driven knee model that incorporated joint kinematics, EMG, and subject-specific muscle volumes and patellar tendon orientation estimated from magnetic resonance imaging. A co-contraction index (CCI) was calculated to quantify the level of co-contraction between knee flexor and extensor muscles. Results: After training, peak hip and knee flexion as well as hip and knee flexion excursions increased significantly. Additionally, participants demonstrated a significant decrease after training in the areas of muscle co-contraction (CCI [mean ± SD], 0.28 ± 0.10 vs 0.18 ± 0.05; P < .001) and peak tibiofemoral compressive force (97.3 ± 8.0 vs 91.3 ± 10.2 N·kg −1 ; P = .044). Conclusion: Increased muscle co-contraction as well as elevated tibiofemoral compressive loads observed in individuals following ACLR can be reduced by using a landing strategy that encourages greater hip and knee flexion. Clinical Relevance: The findings of the current study provide useful information for the growth of rehabilitation and/or intervention programs aimed to decrease knee joint loading to prevent or delay the development of knee osteoarthritis in those who have undergone ACLR.